Gender and the Labour Market: Comparing Austria and Japan - Gudrun Biffl (Austrian Institute of Economic Research (WIFO), 2006)
Japan and Austria are among the OECD countries with an average labour force participation rate but an above average gender gap as far as employment opportunities and earnings are concerned. In Japan, women in the main working age have a fairly large margin of labour resources not employed in the market economy. In Austria in contrast, the proportion of unused labour resources of mature workers is high, and the gender gap is less pronounced than in Japan, which suggests that a different combination of policies is called for to promote economic and employment growth in the face of an ageing society.
Keywords: 330; Weibliche Arbeitskräfte; Gleichberechtigung; Arbeitsmarkt; Australien; Japan